IMPROVING STUDENTS READING COMPREHENSION OF VIII GRADE STUDENTS AT SMP NEGERI 1 DAKO PEMEAN THROUGH HERRINGBONE TECHNIQUE - Mohammad Rafi'i (Jurnal Madako Education, 2018)
This study is conduct to find out whether there is a significant difference between reading comprehension ability of students at SMP Negeri 1 Dako Pemean who are teach by using Herringbone technique. The method use is experimental method. The instrument for collecting the data is a reading comprehension test. It is conduct in one class (VIII C). The data are obtained through a pre-test and post-test. The researcher use SPSS 16.0 program to analyze the data collection. The result of the analysis show that the application of Herringbone technique improve students’ ability in reading comprehension. The mean score of pre-test is 39.30 while in the post-test improve up to 73.43. Moreover the minimum mastery criterion of English lesson is 65 (sixty-five). Then the data of both test are analyzed by using T-test, and the result show that the T-count value is 13.074 greater than T-table value is 2.074. it can be inferred that the application Herringbone technique is very effective to improve students’ ability in reading comprehension. Keywords: Improving, reading comprehension, Herringbone technique